ANALISIS PENGARUH FIRM SIZE DAN PROFITABILITAS TERHADAP ISLAMIC SOCIAL REPORTING (ISR) DENGAN EARNING GROWTH SEBAGAI VARIABEL MODERATING PADA JAKARTA ISLAMIC INDEX (JII) - Hartini, Titin (Universitas Islam Negeri Raden Fatah Palembang, 2018)
This study aims to determine and analyze the effect of Firm Size and Profitability on Islamic Social Reporting, and see whether Earning Growth can strengthen or weaken the relationship between independent variables to the dependent variable. This research takes object in companies registered in Jakarta Islamic Index (JII) for period 2011-2015, amounted to 30 companies and obtained by 12 companies by using purposive sampling technique. Data analysis method used is multiple regression analysis. Based on the results of simultaneous research all the variables berpegaruh against Islamic Social Reporting, but partially, only Firm Size that affect the Islamic Social Reporting. In addition, Earning Growth can not strengthen or weaken the relationship between independent variables and dependent variables.